The influence of the lunar cycle on spontaneous deliveries in historical rural environments. (May 2019) - Marco-Gracia, Francisco J.
Abstract: Background: Many societies and their medical practitioners throughout the world have historically linked lunar phases to the frequency of births. During more recent decades, academics have discussed this alleged relationship using modern data, obtaining differing results. Objectives: The purpose of this study is to analyse the relationship between the phases of the moon and the frequency of deliveries in a rural historical context without electricity, and among women of low nutritional status. These characteristics are similar to some current rural areas in certain developing countries. The exceptionality of this case will allow us to test several of the existing theories on how the moon could influence births, particularly those related to lunar light. We will also analyse nulliparous and multiparous differences over the very long term. Study design: This study is a retrospective cohort analysis. In total, 23, 689 births have been considered for 1484 lunar cycles between 1810 and 1929. Birth registers have been obtained from the Catholic parish archives of 10 rural Spanish agrarian villages. All the deliveries analysed were natural, without any medical follow-up, within the home and with little medical assistance. Results: Using simple descriptive statistical techniques, we can conclude that there is no pattern with which to link lunar phases with the frequency of births. We can also conclude that neither electricity nor the rural environment affects this alleged relationship; neither have we found any relationship related to either the nulliparous or the multiparous and lunar phases. Conclusion: The analysis of a 120-year period has shown that there is no predictable influence of the lunar phases on the frequency of births. The myth of such a lunar influence can claim no scientific evidence from a historical perspective. Neither the arrival of the electric light nor the lower number of deliveries per woman have modified birth patterns. Deliveries by rural women of low nutritional status are not linked to the phases of the moon, and consequently the medical services in developing countries should disregard this belief; they do not need to take account of the phases of the moon with respect to their daily organisation.